Decrease in hand and cerebral oxygenation after percutaneous transluminal angioplasty for arteriovenous fistula stenosis in a patient on chronic hemodialysis - Shindo, Mitsutoshi; Ookawara, Susumu; Kovarova, Lucie; Morino, Junki; Minato, Saori; Ito, Kiyonori; Malik, Jan; Morishita, Yoshiyuki (Radiology case reports, 2020)
A 79-year-old woman who was on chronic hemodialysis due to diabetic nephropathy and had previously undergo surgery for radiocephalic arteriovenous fistula (AVF) in her right wrist needed percutaneous transluminal angioplasty (PTA) for stenosis at the juxta-anastomotic access site. After successful PTA, the systemic blood pressure decreased from 144/93 mm Hg to 117/67 mm Hg in response to the increase in AVF blood flow. Furthermore, the regional oxygen saturation (rSO2) value in her dorsal hand decreased from 67.9% to 64.9% and, simultaneously, the cerebral rSO2 decreased from 63.6% to 60.1%. Our experience indicates that the PTA procedure may affect the rapid deterioration of systemic oxygenation, including that in the hand and brain, in association with the increase in the AVF blood flow and change in systemic circulation.
Keywords: Percutaneous transluminal angioplasty; Hand oxygenation; Hemodialysis; Cerebral oxygenation; Hemodynamic instability; Arteriovenous fistula